A Simple and Scalable Method for the Preparation of Magnetite/Graphene Oxide Nanocomposites under Mild Conditions - Tamás Szabó; Lilla Nánai; Dániel Nesztor; Balázs Barna; Ondřej Malina; Etelka Tombácz (Advances in Materials Science and Engineering)
Nanostructured composite dispersions containing magnetic nanoparticles (MNPs) and graphene oxide (GO) lamellae have been prepared by a simple and easily scalable room temperature procedure. We show that, owing to the enormous surface area and negative surface charge developed in aqueous GO suspensions, large amounts of positively charged MNPs can be electrostatically attached to the layered host. This procedure is superior to many previous synthesis pathways because it exploits the charge-regulated adhesion of naked MNPs to GO resulting in the formation of stable and uniform nanocomposite materials in a wide composition range without any preliminary functionalization steps or harsh conditions that may lead to chemical degradation of the graphene-based nanosheets.